(untitled) (Dhaka University Law Journal, 2025)
Water, as a core component of natural environment, requires ensuring its wise management along with other core components of environment. As a segment of environmental management (EM), water resource management (WRM) should be holistic and sustainable, for which ‘integrated water resource management’ (IWRM) is considered globally as an effective tool. There is a linkage between EM and WRM; and IWRM is practiced in many countries as a WRM mechanism. In Bangladesh context, preserving country’s deltaic character and protecting the aquatic ecosystem require designing and implementing IWRM in a prudent manner which may lead to attain sound EM. Invariably, such implementation is a pressing concern for Bangladesh, as complex issues are associated with their applications. The challenges derive substantially from various developmental activities which have been taken, disregarding factors associated with the protection of the natural environment and aquatic ecosystem. Bangladesh has enacted ample of sector-based laws and policies, having direct and indirect bearing on WRM and EM, but these sectoral laws also have some lacking. The deteriorating state of overall natural environment, especially of the aquatic ecosystem, also corroborates the failure of the relevant governmental organizations to perform their statutory responsibilities. Therefore, this research article largely attempts to explore the linkage among the EM, WRM and IWRM, and their reflections in two vital water laws of Bangladesh along with their gaps and challenges. Upon reviewing different literature on these concepts, and analysing the Bangladesh Water Act 2013 and Bangladesh Water Rules 2018, it is found that the IWRM principles as prescribed internationally have fair reflections in these two national laws, though not all these principles have been recognized. Moreover, the IWRM principles which are already mentioned in these two national laws are, in most cases, applied lightly or even non-implemented, because of the relaxed exercise of institutional good governance, which is a persistent challenge for Bangladesh, affecting to secure sound EM as a whole. Dhaka University Law Journal Vol.35, Issue.2, December 2024 P. 167-190